Experimental Characterization and Modeling Microwave Heating of Oil Palm Fruits and Bunches - Chang, Sze Ling Jessie (Curtin University, 2017)
The implementation of microwave in oil palm processing operations provides extensive heat generation to accelerate the removal of moisture compared to the conventional method. The characterizations and the effects of microwave heating on oil palm fruits and bunches are investigated. In addition, a multi-physics model is developed to further investigate the microwave energy interaction with the oil palm fruits and bunches.